(untitled) (Acta Polytechnica CTU Proceedings, 2022)
The COVID-19 pandemic meant that people had to perform most of their daily activities from home. This study intends to investigate if a period of working from home has changed living preferences concerning housing size and location. The data was collected through a web-based survey. The literature is divided regarding the potential benefits of reduced commuting due to increased home office utilization. There is a prevalent risk of rebound effects as saved travel time might lead to increased travel on leisure, which could counterweight the benefits of reduced daily commuting in cities. Most of the respondents in this study want to work from home 2-3 days a week. The respondents that desire to move to a less central location state the lower square meter price as one important reason. Analyses in prevailing research did not investigate the preference for larger homes combined with increased home office use. Future studies should also investigate the desire for larger homes to achieve a holistic evaluation of the emissions related to telecommuting.